Public-Utility Regulators Are Only Human: A Positive Theory of Rational Constraints - Evans, Lewis; Garber, Steven (American Economic Review, 1988)
Positive models of public-utility regulation should capture personal incentives of regulators. A regulatory objective function is specified by appea l to standard human concerns coupled with politics and processes pecu liar to public-utility regulation. Constraints a rational regulator w ould impose on the firm are thereby derived, and connections between regulatory objectives and regulatory rules illuminated. Results inclu de theoretical rationales for "rate-of-return" regulation in a worl d of certainty, and a largely neglected type of "rate-of-return" re gulation under (symmetric) uncertainty. Other forms of regulation sho uld also be explicable in terms of personal motives of human regulato rs. Copyright 1988 by American Economic Association.